Molecular Docking and Molecular Dynamic Investigations of Xanthone-Chalcone Derivatives against Epidermal Growth Factor Receptor for Preliminary Discovery of Novel Anticancer Agent - Yehezkiel Steven Kurniawan; Ervan Yudha; Gerry Nugraha; Nela Fatmasari; Harno Dwi Pranowo; Jumina Jumina; Eti Nurwening Sholikhah (Indonesian Journal of Chemistry, 2024)
Epidermal growth factor receptor (EGFR) is found to be overexpressed in cancer cells as it controls angiogenesis, cell signaling, and proliferation mechanisms. Therefore, EGFR has been known as a common target for the initial screening of new anticancer agents. Either xanthone or chalcone has been evaluated as the anticancer agents, and their activity strongly depends on the type and position of the attached functional group. Therefore, molecular hybridization between xanthone and chalcone could yield novel anticancer agents through the EGFR inhibition mechanism. Herein, a series of xanthone-chalcone derivatives with hydrogen-bond-acceptor or hydrogen-bond-donor substituents at ortho, meta, and para positions was evaluated as the EGFR inhibitor. Thirty-seven xanthone-chalcones were designed and docked in the active site of EGFR. Compared to the native ligand, pristine xanthone-chalcone gave a 1.215× stronger binding energy and a 13.97× lower binding constant. Compound 3SH was found to be the most promising candidate due to its strongest binding energy (−9.71 kcal/mol) and the lowest binding constant (0.08 µM). Furthermore, molecular dynamic studies demonstrated that complex EGFR-3SH was stable for 100 ns simulation. These in silico investigations show that the xanthone-chalcone derivative is a promising novel anticancer agent to be examined through in vitro and in vivo assays.